“If They Did Not Exist They Would Have To Be Invented” – The Role of Immigrants and Their Regulation in the American Socio-Political Context - Ilc, Blaž (Two Homelands, 2012)
The article explores the multidimensional, heterogeneous and complex role that immigrants and their regulation played and play in the American socio-political context. It argues that immigrants have played and play a crucial role in the establishment and development of the American republic. They were and are crucial for the continuous re-inscriptions of symbolic and material boundaries of the American na- tion and citizenship and in the development of the capacities and legitimacy of state apparatuses to regulate the US population. They are also indispensable for the functioning of the American economy.